Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1002/jps.21878
|View full text |Cite
|
Sign up to set email alerts
|

Effluxing ABC transporters in human corneal epithelium

Abstract: ATP-binding cassette (ABC) transporters are able to efflux their substrate drugs from the cells. We compared expression of efflux proteins in normal human corneal epithelial tissue, primary human corneal epithelial cells (HCEpiC), and corneal epithelial cell culture model (HCE model) based on human immortal cell line. Expression of multidrug resistance protein 1 (MDR1), multidrug resistance-associated protein 1-6 (MRP1-6) and breast cancer resistance protein (BCRP) was studied using quantitative RT-PCR, Wester… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
58
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(68 citation statements)
references
References 64 publications
(67 reference statements)
6
58
4
Order By: Relevance
“…Functional activity of some efflux transporters has also been evaluated, but the results of efflux transporter expressions and functions were very different. Dey et al (2003) and Becker et al (2007) investigated the mRNA expression of MDR1 in human corneas, as well as the MDR1 expression in a human corneal cell line by Western blotting, but no detectable or very low MDR1 mRNA and/or protein expressions were observed in human corneas according to other reports (Dey et al, 2003; dmd.aspetjournals.org Becker et al, 2007), and these discrepancies may be due to variation in sensitivity of different experimental methods and different tissues used (Vellonen et al, 2010). Regarding the function of efflux transporters, Dey et al (2003) evaluated the functional activity of MDR1 efflux pump with cultured rabbit primary corneal epithelial cells and a corneal cell line (Statens Seruminstitut rabbit cornea [SIRC] cells) as the model, with the results that MDR1 affected corneal uptake.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Functional activity of some efflux transporters has also been evaluated, but the results of efflux transporter expressions and functions were very different. Dey et al (2003) and Becker et al (2007) investigated the mRNA expression of MDR1 in human corneas, as well as the MDR1 expression in a human corneal cell line by Western blotting, but no detectable or very low MDR1 mRNA and/or protein expressions were observed in human corneas according to other reports (Dey et al, 2003; dmd.aspetjournals.org Becker et al, 2007), and these discrepancies may be due to variation in sensitivity of different experimental methods and different tissues used (Vellonen et al, 2010). Regarding the function of efflux transporters, Dey et al (2003) evaluated the functional activity of MDR1 efflux pump with cultured rabbit primary corneal epithelial cells and a corneal cell line (Statens Seruminstitut rabbit cornea [SIRC] cells) as the model, with the results that MDR1 affected corneal uptake.…”
Section: Discussionmentioning
confidence: 97%
“…In 2003, Dey et al (2003) found, for the first time, that the human cornea can express MDR1. Since then, individual efflux transporters in human and animal corneas and corneal epithelial cells have been widely investigated (Karla et al, 2007a(Karla et al, ,b, 2009Pelis et al, 2009;Vellonen et al, 2010;Barot et al, 2011;Li et al, 2012). Functional activity of some efflux transporters has also been evaluated, but the results of efflux transporter expressions and functions were very different.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To elucidate the role of MRP 1 and MRP 3 on the protein level, a modified protocol from Vellonen et al 16 was used. Briefly, 7 × 10 6 BT474 cells were suspended in a protein lysis buffer (1% [v/v] Triton X-100, 20 mM Tris-HCl, 150 mM NaCl, 1 mM EDTA) for 30 minutes on ice and centrifuged for 30 minutes at 10,000 g (4°C) to decant cell detritus and nuclei.…”
Section: Mrp 1 and Mrp 3 Protein Expressionmentioning
confidence: 99%